GEOGRAPHIC INFORMATION SYSTEM APPLICATION TO ANALYZE TOLERATED EROSION FLOW IN MAMASA CATCHMENT AREA - Faridah, Sitti Nur (Badan Informasi Geospasial in Partnership with MAPIN, 2009)
Geographic information system currently used in various fields, such as land suitability mapping, erosion studies and transmission network planning. To study the estimated amount of erosion of soil loss can be easily obtained by calculating and overlaying maps which are components of Modified Universal Soil Loss Equation (MUSLE). GIS applications of the results obtained less than 35% of the watershed has Mamasa erosion rate is still tolerable, which is the region with the use of forest land and paddy fields, with a value of TSL 22.17 tons/ha/yr. Keywords: GIS. Erosion, Watershed Mamasa ABSTRAK Sistem informasi geografis saat ini banyak digunakan diberbagai bidang, seperti pemetaan kesesuaian lahan, studi erosi dan perencanaan jaringan transmisi. Untuk studi erosi estimasi besarnya kehilangan tanah dapat dengan mudah diperoleh dengan mengkalkulasi dan overlay peta yang merupakan komponen Modified Universal Soil Loss Equation (MUSLE). Dari hasil aplikasi SIG diperoleh kurang dari 35 % wilayah DAS Mamasa mempunyai laju erosi yang masih dapat ditoleransi, yang terdapat pada wilayah dengan penggunaan lahan hutan dan persawahan, dengan nilai TSL 22,17 ton/ha/thn. Kata Kunci : SIG. Erosi , DAS Mamasa